Preparation method of lithium battery-structure integrated material

The preparation of nanoconductive adhesives and solid nanoadhesive agents through the dual emulsion method solves the problems of low adhesive efficiency and poor thermal stability of the separator in lithium batteries. Through the design of battery-structure integrated materials, the lightweight and performance improvement of lithium batteries are achieved.

CN119864374AActive Publication Date: 2025-04-22HARBIN INST OF TECH

Patent Information

Application Number
CN202510160481.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-01-31
Publication Date
2025-04-22
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

The bonding efficiency of the adhesive in existing lithium batteries is low, affecting the electron transfer efficiency; the polyolefin separator has poor thermal stability and poor liquid retention performance; and the weight problems of lithium batteries when used in the aviation field.

Method used

The dual emulsion method is used to prepare nanoconductive adhesives, and dry bonding is achieved through the combination of surface reactive activity and latent curing agent; at the same time, solid nanoadhesive adhesives are prepared by the emulsion method of epoxy resin and electrolyte solution to improve the thermal stability and porosity of the separator; and the design of a self-adhesive battery-structure integrated composite material to reduce the weight load of the aircraft.

Benefits of technology

The efficient preparation of lithium battery dry electrodes is achieved, the bonding strength and electron transmission efficiency are improved; the thermal stability and porosity of the lithium battery separator are improved, and the battery performance is improved; and the lightweight of lithium batteries is achieved through the design of battery-structure integrated material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864374A_ABST
    Figure CN119864374A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a lithium battery-structure integrated composite material, and belongs to the technical field of lithium battery preparation. The method comprises the following steps: uniformly mixing epoxy resin, a diluent, a curing agent 1 and a lipophilic emulsifier to obtain a dispersion liquid 1; dropwise adding an electrolyte solution into the dispersion liquid 1 at a constant speed, and stirring at a constant temperature and a high speed to obtain a water-in-oil emulsion; uniformly mixing deionized water, a hydrophilic emulsifier and a curing agent 2 at a constant temperature to obtain dispersion liquid 2; adding the water-in-oil emulsion into the dispersion liquid 2, and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system; heating and curing the water-in-oil-in-water emulsion system; after curing, centrifuging, washing and drying to obtain a solid nano adhesive; and grinding the solid nano adhesive, and then uniformly paving the solid nano adhesive in a mold for high-temperature treatment to obtain the lithium battery diaphragm. The electrolyte solution is selected as the internal water phase of the water-in-oil emulsion, so that the internal osmotic pressure of the emulsion can be increased, the emulsion is prevented from being fused, and the particle size is increased.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with application date of January 31, 2023, application number 2023100479284, and invention name “A method for preparing dry electrodes, diaphragms and battery-structure integrated materials for lithium batteries”. Technical Field

[0002] The present invention belongs to the technical field of lithium battery preparation, and in particular relates to a method for preparing a lithium battery dry electrode, a diaphragm and a battery-structure integrated material. Background Art

[0003] The preparation of lithium-ion battery electrodes is achieved by mixing electrode active materials, conductive agents and adhesives evenly and then coating them on metal current collectors. The electrode active materials determine the energy density of the battery. Conductive agents can improve the transmission efficiency of electrons in the electrode, thereby improving the specific capacity and rate charge and discharge capacity of the battery. The main purpose of the adhesive is to adhere the electrode active materials and conductive agents to the metal current collector to ensure the formation of a stable pole piece structure. As one of the inactive components of the positive and negative electrode materials of lithium-ion batteries, although the adhesive accounts for only 1.5% to 3% of the total mass of the electrode material, it plays a very important role in affecting the overall electrochemical performance of the battery. Therefore, it can also be said that the adhesive is a decisive battery component in lithium-ion batteries, which has a great influence on the actual capacity, rate capability and cycle life of the battery.

[0004] At present, there are two main types of adhesives: one is an organic solvent-soluble adhesive represented by polyvinylidene fluoride, and the other is a water-soluble adhesive represented by carboxymethyl cellulose / styrene butadiene rubber. The common characteristics of the two are that they both require the participation of liquid solvents, and the adhesives are all inactive ingredients, which may have adverse effects on the efficiency of electron transmission. Therefore, it is of great practical significance to develop a conductive adhesive that can achieve complete dry bonding, thereby realizing the successful preparation of dry electrodes for lithium batteries.

[0005] The diaphragm is a key component of liquid lithium-ion batteries. Current liquid lithium-ion batteries mainly use non-aqueous liquid electrolytes, and a porous diaphragm is used between the positive and negative electrodes to isolate the positive and negative electrodes to prevent short circuits. At the same time, lithium ions can be conducted in the electrolyte through the pores inside the diaphragm. As a diaphragm for lithium-ion batteries, it must not only isolate the positive and negative electrodes, but also meet the requirements of other parameters (liquid absorption rate, porosity, electrochemical stability, thermal stability, mechanical properties, etc.). At present, diaphragms are mainly divided into commercial polyolefin diaphragms, polyolefin modified diaphragms, and non-woven diaphragms. However, there are currently many technical bottlenecks. For example, the essential characteristics of polyolefins cause their poor thermal stability, thermal shrinkage at high temperatures that causes the risk of battery short circuits, and poor liquid absorption and retention performance.

[0006] With the continuous progress of aviation technology, the growth of air traffic has generally shown a clear upward trend. The growth of air traffic will lead to an increase in fuel combustion and aggravation of air traffic's environmental pollution. The aviation industry (manufacturers and operators) is now introducing new technologies and operational solutions to reduce the fossil fuels consumed by aircraft. However, it will take many years to reach the stage where all aircraft are replaced by a new generation of transportation. An electric aircraft is an aircraft that uses an electric motor as a power unit, and the power supply source includes batteries such as batteries, fuel cells, solar cells, and supercapacitors. Currently, the more successful manned electric aircraft mainly use batteries (mainly lithium battery electric aircraft), solar cells (called solar aircraft) or fuel cells as power supply sources. Electric propulsion systems have many important features, such as the high efficiency of its energy conversion chain, and some of them can even achieve zero emissions.

[0007] However, the difficulty of applying electric propulsion systems in the aviation field is significantly higher than that in ground transportation. Because ground transportation can well solve the problem of extra weight caused by imperfect electric energy storage and propulsion technology, while aircraft are very sensitive to weight. Therefore, a battery-structure integrated composite material is developed. By designing lithium batteries as self-adhesive integrated composite materials, lithium batteries are perfectly combined with composite materials such as wings, thereby reducing the weight of the aircraft itself and achieving lightweight electric aircraft. Summary of the invention

[0008] The purpose of the present invention is to solve the problems of low bonding efficiency of lithium battery binders and adverse effects on electron transmission efficiency, poor thermal stability of polyolefin diaphragms, poor liquid absorption and retention performance, and lightweight lithium batteries, and to provide a method for preparing dry electrodes, diaphragms and battery-structure integrated materials for lithium batteries.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a dry-process electrode for a lithium battery, the method comprising the following steps:

[0011] Step 1, uniformly mix and disperse the conductive nanoparticles, epoxy resin, diluent, curing agent 1 and lipophilic emulsifier to obtain dispersion 1;

[0012] Step 2: dripping the electrolyte solution into the dispersion 1 at a constant speed, stirring at a constant temperature and high speed to obtain a water-in-oil emulsion;

[0013] Step 3: at a constant temperature, uniformly mix and disperse deionized water, a hydrophilic emulsifier and a curing agent 2 to obtain a dispersion 2;

[0014] Step 4: adding the water-in-oil emulsion to the dispersion 2, and continuously stirring and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system;

[0015] Step 5: heating the water-in-oil-in-water emulsion system, stirring continuously, and solidifying;

[0016] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to obtain a nano-conductive adhesive;

[0017] Step 7: Evenly mix the nano-conductive adhesive, active material and conductive agent and grind them thoroughly, spread the mixed powder on aluminum foil, and press it into shape using a hot press at high temperature to obtain a lithium battery electrode.

[0018] A method for preparing a lithium battery separator, the method comprising the following steps:

[0019] Step 1, uniformly mix and disperse the epoxy resin, diluent, curing agent 1 and lipophilic emulsifier to obtain dispersion 1;

[0020] Step 2: dripping the electrolyte solution into the dispersion 1 at a constant speed, stirring at a constant temperature and high speed to obtain a water-in-oil emulsion;

[0021] Step 3: at a constant temperature, uniformly mix and disperse deionized water, a hydrophilic emulsifier and a curing agent 2 to obtain a dispersion 2;

[0022] Step 4: adding the water-in-oil emulsion to the dispersion 2, and continuously stirring and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system;

[0023] Step 5: heating the water-in-oil-in-water emulsion system, stirring continuously, and solidifying;

[0024] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to obtain a solid nano-adhesive;

[0025] Step seven: Grind the solid nano adhesive, and then evenly spread it in a stainless steel groove mold. Use a hot press to treat it at a certain pressure and high temperature to obtain a lithium battery separator.

[0026] A method for preparing a battery-structure integrated composite material comprising the lithium battery separator prepared above, the method further comprising:

[0027] Step 8: Evenly mix the nano adhesive, positive electrode active material, and conductive agent and grind them thoroughly, spread the mixed powder on aluminum foil, and press them into shape using a hot press at high temperature to obtain a positive electrode for a lithium battery;

[0028] Step nine: uniformly mix the nano adhesive, negative electrode active material, and conductive agent and grind them thoroughly, spread the mixed powder on the copper foil, and press it into shape using a hot press at high temperature to obtain the negative electrode of the lithium battery;

[0029] Step 10: Stack the negative electrode sheet, separator, electrolyte solution and positive electrode sheet in order from bottom to top, and use a hot press to form them into an integrated whole at high temperature.

[0030] The beneficial effects of the present invention compared to the prior art are:

[0031] (1) The present invention realizes the synthesis of dry-process lithium battery electrodes. The nano-conductive adhesive prepared first can achieve self-adhesion through post-curing reaction at a specific temperature due to the retention of surface reaction activity and the presence of a latent curing agent. Then, the adhesive is used to achieve dry-process bonding of lithium battery electrodes. Unlike most electrode adhesives, the nano-conductive adhesive in the present invention not only does not require any solvent participation and has high bonding strength, but also can retain a large number of holes after bonding for electron transmission.

[0032] (2) The present invention imparts excellent conductivity to the adhesive by adding conductive nanoparticles, which largely avoids the obstruction to electron transmission caused by traditional inactive insulating adhesives.

[0033] (3) The present invention uses two different curing agents at the same time, taking advantage of the differences in chemical properties and curing processes of different types of curing agents, so that curing agent 2 acts on epoxy particles to cure and form, thereby achieving successful latent curing of curing agent 1.

[0034] (4) The present invention uses an electrolyte solution as the internal water phase of the water-in-oil emulsion. Firstly, it can increase the internal osmotic pressure of the emulsion to prevent fusion between the emulsions and increase the particle size. Secondly, some electrolytes have a catalytic effect on the ring-opening reaction of the epoxy group of the epoxy resin, which can accelerate the formation of the spherical particles of the epoxy resin.

[0035] (5) In step 3 of the present invention, the hydrophilic emulsifier is selected from a combination of a nonionic emulsifier and an anionic emulsifier. Under appropriate proportions, a better emulsification effect on the water-in-oil emulsion is achieved.

[0036] (6) In the curing process of the epoxy resin spherical particles in steps 4 and 5 of the present invention, a gradual temperature increase is adopted instead of directly applying the optimal curing temperature of the curing agent, which avoids the destruction of the water-in-oil-in-water emulsion by the sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution.

[0037] (7) In the present invention, the lithium battery electrode is prepared by hot pressing, which can make the thickness of the electrode sheet uniform and increase the compaction density of the negative electrode material. The appropriate compaction density can increase the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the lithium-ion battery.

[0038] (8) Epoxy resin has excellent mechanical properties and strong chemical resistance, and has stronger temperature resistance than conventional separators. Since the adhesive is in the form of spherical particles, a large number of holes will be formed during the self-adhesive film-forming process. The high porosity of the separator is the basic guarantee for the efficiency of lithium batteries. In addition, the pore size of the separator can also be adjusted by the particle size of the solid adhesive.

[0039] (9) The present invention first innovatively realizes the synthesis of nano adhesives, the minimum particle size of which can reach 50nm. Due to the retention of surface reactivity and the presence of latent curing agent, self-adhesion can be achieved through post-curing reaction at a specific temperature. Unlike most adhesives, the nano adhesive in the present invention not only has high bonding strength, but also can retain a large number of pores after bonding.

[0040] (10) The present invention develops a battery-structure integrated composite material. By designing the lithium battery as a self-adhesive integrated composite material, the lithium battery can be directly used in various supporting structures, thereby reducing the load of the supporting structure itself and achieving structural lightweight. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of lithium battery electrodes prepared by dry method.

[0042] Figure 2 This is the cyclic voltammetry curve of the dry electrode of a lithium battery.

[0043] Figure 3 This is the SEM image of the nano-adhesive.

[0044] Figure 4 This is a picture of the lithium battery separator obtained by self-adhesion of solid nanoadhesive.

[0045] Figure 5 This is the SEM image of the lithium battery separator obtained by self-adhesion of solid nanoadhesive.

[0046] Figure 6 Schematic diagram of the battery-structure integrated composite material structure. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further illustrated below through the drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0048] Specific implementation method 1: This implementation method describes a method for preparing a dry-process electrode for a lithium battery, and the method steps are as follows:

[0049] Step 1: uniformly mix and disperse the conductive nanoparticles, epoxy resin, diluent, curing agent 1 and lipophilic emulsifier using a high-speed disperser to obtain a dispersion 1;

[0050] Step 2: dripping the electrolyte solution into the dispersion 1 at a constant speed, stirring at a constant temperature and high speed to obtain a water-in-oil emulsion;

[0051] Step 3: at a constant temperature, deionized water, a hydrophilic emulsifier and a curing agent 2 are uniformly mixed and dispersed using a high-speed disperser to obtain a dispersion 2;

[0052] Step 4: adding the water-in-oil emulsion to the dispersion 2, and continuously stirring and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system;

[0053] Step 5: heating the water-in-oil-in-water emulsion system, stirring continuously, and adjusting the curing temperature and time to control the epoxy resin balls to form nanoparticles and retain more reactive groups;

[0054] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to obtain a nano-conductive adhesive;

[0055] Step 7: Evenly mix and fully grind the nano-conductive adhesive, active material, and conductive agent, spread the mixed powder on aluminum foil, and press it into shape using a hot press at high temperature to obtain a lithium battery electrode. This method uses a double emulsion method, conductive particle filling, and a curing agent to successfully obtain a nano-scale solid conductive adhesive, and then achieves dry bonding of lithium battery electrodes without any solvent.

[0056] Specific embodiment 2: A method for preparing a dry electrode for a lithium battery as described in specific embodiment 1, in step 1, the conductive nanoparticles are at least one of silver nanoparticles, gold nanoparticles, copper nanoparticles, graphene, carbon nanotubes, conductive graphite, conductive carbon black, and carbon fibers; the epoxy resin is at least one of bisphenol A epoxy resin, glycidyl ester epoxy resin, and alicyclic epoxy resin; the bisphenol A epoxy resin is at least one of E55, E51, and E44; the glycidyl ester epoxy resin is at least one of 711#, TDE-85#, and 731#; the alicyclic epoxy resin is at least one of W-95#, 6221#, and 6206#; the diluent is at least one of ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, and butyl glycidyl ether; the curing agent is at least one of ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, and butyl glycidyl ether; the curing agent is at least one of ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, and butyl glycidyl ether. Agent 1 is at least one of maleic anhydride, phthalic anhydride, m-phenylenediamine, 3,3'-diethyl-4,4'-diaminodiphenylmethane and 4,4'-diaminodiphenylmethane. The present invention mainly utilizes the fact that the above-mentioned high-temperature curing agent will not react under low-temperature treatment during the processing of the nano adhesive, thereby achieving successful latent properties; the lipophilic emulsifier is at least one of Span 20, Span 40, Span 60 and Span 80; the mass ratio of the epoxy resin to the conductive nanoparticles is 100:1-5; the mass ratio of the epoxy resin to the diluent is 3-6:1; the mass ratio of the epoxy resin to the curing agent 1 is 10:2-3, and the amount is based on the theoretical amount of curing agent 1 for curing the epoxy resin; the mass ratio of the epoxy resin to the lipophilic emulsifier is 5:2-5; in step 2, the mass ratio of the epoxy resin to the electrolyte solution is 5:2-5.

[0057] Specific embodiment three: A method for preparing a dry electrode for a lithium battery as described in specific embodiment one, in step two, the electrolyte solution is at least one of a 0.1 mol / L sodium chloride solution, a 0.1 mol / L potassium chloride solution, a pH=10 NH3·H2O-NH4Cl buffer solution and a 0.1 mol / L sodium hydroxide solution; the constant reaction temperature is 40-60°C, the time is 10-15 min, and the stirring speed is 2500-3000 rpm.

[0058] Specific embodiment 4: A method for preparing a dry-process electrode for a lithium battery as described in specific embodiment 1, in step 3, the hydrophilic emulsifier is one or a mixture of a nonionic emulsifier and an anionic emulsifier; either a single nonionic emulsifier or an anionic emulsifier can achieve emulsification, but a combination may have a better effect; the nonionic emulsifier is at least one of polyoxyethylene ether, OP-10 and polyvinyl alcohol; the anionic emulsifier is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and phosphate; the curing agent 2 is ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylene One or a mixture of olefinic pentamines; curing agent 2 needs to use some fatty amine curing agents with lower curing temperature, because this type of curing agent must achieve partial curing of epoxy nano adhesive at a low temperature where curing agent 1 will not react; the mass ratio of deionized water to hydrophilic emulsifier is 15-20:1; the mass ratio of nonionic emulsifier to anionic emulsifier is 20:0-3; the mass ratio of deionized water to curing agent 2 is 30-40:1; the amount is based on the theoretical amount of curing agent 2 for curing epoxy resin; in step 4, the mass ratio of deionized water to water-in-oil emulsion is 15-20:1.

[0059] Specific embodiment five: A method for preparing a dry electrode for a lithium battery as described in specific embodiment one, wherein the constant temperature in step three is 40-50°C; in steps four and five, the stirring speed is 1000-1500rpm; in step five, the temperature is raised to 60-80°C, and the heating process is carried out with insulation reaction for a total of 25-30 minutes; in step seven, the high temperature is the curing temperature of the curing agent 1, and the hot press pressure is 2-4MPa; in step seven, the active material is at least one of graphite, lithium titanate, and silicon-carbon alloy; the conductive agent is at least one of acetylene black, conductive carbon black, and Super P; the mass ratio of the nano conductive adhesive to the active material is 1-3:17, and the mass ratio of the nano conductive adhesive to the conductive agent is 1-2:1.

[0060] Specific embodiment 6: This embodiment describes a method for preparing a lithium battery separator, and the method steps are as follows:

[0061] Step 1, uniformly mix and disperse the epoxy resin, diluent, curing agent 1 and lipophilic emulsifier using a high-speed disperser to obtain a dispersion 1;

[0062] Step 2: dripping the electrolyte solution into the dispersion 1 at a constant speed, stirring at a constant temperature and high speed to obtain a water-in-oil emulsion;

[0063] Step 3: at a constant temperature, deionized water, a hydrophilic emulsifier and a curing agent 2 are uniformly mixed and dispersed using a high-speed disperser to obtain a dispersion 2;

[0064] Step 4: adding the water-in-oil emulsion to the dispersion 2, and continuously stirring and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system;

[0065] Step 5: heating the water-in-oil-in-water emulsion system, stirring continuously, and adjusting the curing temperature and time to control the epoxy resin balls to form nanoparticles and retain more reactive groups;

[0066] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to obtain a solid nano-adhesive;

[0067] Step 7: Grind the solid nano adhesive, then evenly spread it in a stainless steel groove mold, and use a hot press to treat it at a certain pressure and high temperature to obtain a lithium battery separator. The nanoscale self-adhesive epoxy resin adhesive is obtained by using a double emulsion method and a successful latent curing agent, and the adhesive is self-adhesive to form a film by high temperature treatment. Since the solid adhesive is a cured epoxy resin, the thermal stability, chemical corrosion resistance and mechanical properties are very excellent. In addition, the porosity of the spherical adhesive is high during the self-adhesive film forming process.

[0068] Specific embodiment seven: A method for preparing a lithium battery separator described in specific embodiment six, in step one, the epoxy resin is at least one of bisphenol A epoxy resin, glycidyl ester epoxy resin and alicyclic epoxy resin; the bisphenol A epoxy resin is at least one of E55, E51 and E44; the glycidyl ester epoxy resin is at least one of 711#, TDE-85# and 731#; the alicyclic epoxy resin is at least one of W-95#, 6221# and 6206#; the diluent is at least one of ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, butyl glycidyl ether; the curing agent 1 is maleic anhydride, phthalic anhydride, One or a mixture of m-phenylenediamine, 3,3'-diethyl-4,4'-diaminodiphenylmethane and 4,4'-diaminodiphenylmethane. The present invention mainly utilizes the fact that the above-mentioned high-temperature curing agent will not react under low-temperature treatment during the processing of the nano adhesive, thereby achieving successful latent properties; the lipophilic emulsifier is at least one of Span 20, Span 40, Span 60 and Span 80; the mass ratio of the epoxy resin to the diluent is 3-6:1; the mass ratio of the epoxy resin to the curing agent 1 is 10:2-3, and the amount is based on the theoretical amount of curing agent 1 for curing the epoxy resin; the mass ratio of the epoxy resin to the lipophilic emulsifier is 5:2-5; in step 2, the mass ratio of the epoxy resin to the electrolyte solution is 5:2-5.

[0069] Specific embodiment eight: A method for preparing a lithium battery separator as described in specific embodiment six or seven, in step two, the electrolyte solution is at least one of a 0.1 mol / L sodium chloride solution, a 0.1 mol / L potassium chloride solution, a pH=10 NH3·H2O-NH4Cl buffer solution and a 0.1 mol / L sodium hydroxide solution; the constant reaction temperature is 40-60°C, the reaction time is 10-15 min, and the stirring speed is 2500-3000 rpm. In step three, the initial temperature is 40-50°C; in step five, the temperature is raised to 60-80°C, and the heating process plus the heat preservation reaction is 25-30 minutes in total; the stirring speed is 1000-1500 rpm; in step seven, the amount of solid nano adhesive is 0.02-0.05g; the high temperature is the curing temperature of curing agent 1; at this temperature, curing agent 1 will react with the epoxy group of the epoxy resin, thereby causing a cross-linking reaction between epoxy nanoparticles; the size of the stainless steel mold groove is 40*40*10mm 3 ; When evenly coating the nano adhesive, use a coating knife to initially control its thickness to 0.05-0.1mm; the hot press pressure is 1-2MPa.

[0070] Specific embodiment 9: A method for preparing a lithium battery separator as described in specific embodiment 6, in step 3, the hydrophilic emulsifier is one or a mixture of a nonionic emulsifier and an anionic emulsifier; either a single nonionic emulsifier or an anionic emulsifier can achieve emulsification, but the effect may be better when used in combination; the nonionic emulsifier is at least one of polyoxyethylene ether, OP-10 and polyvinyl alcohol; the anionic emulsifier is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and phosphate; the curing agent 2 is ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine one or a mixture; curing agent 2 needs to use some fatty amine curing agents with lower curing temperature, because this type of curing agent must achieve partial curing of the epoxy nano adhesive at a low temperature where curing agent 1 will not react; the mass ratio of deionized water to hydrophilic emulsifier is 15-20:1; the mass ratio of nonionic emulsifier to anionic emulsifier is 20:0-3 (if used in combination); the mass ratio of deionized water to curing agent 2 is 30-40:1; the amount is based on the theoretical amount of curing agent 2 for curing epoxy resin; in step 4, the mass ratio of deionized water to oil-in-water emulsion is 15-20:1.

[0071] Specific embodiment 10: A method for preparing a battery-structure integrated composite material including a lithium battery separator prepared according to any one of specific embodiments 6 to 9, the method further comprising:

[0072] Step 8: Evenly mix the nano adhesive, the positive electrode active material, and the conductive agent and grind them thoroughly, spread the mixed powder on the aluminum foil, and press the mixture into shape using a hot press at high temperature to obtain the positive electrode of the lithium battery; the positive electrode active material is at least one of lithium manganese oxide, lithium cobalt oxide, and nickel-cobalt-manganese ternary material; the conductive agent is at least one of acetylene black, conductive carbon black, and Super P; the mass ratio of the nano adhesive to the positive electrode active material is 1-3:17, and the mass ratio of the nano adhesive to the conductive agent is 1-2:1;

[0073] Step nine: uniformly mix the nano adhesive, negative electrode active material, and conductive agent and grind them thoroughly, spread the mixed powder on the copper foil, and press the mixture into shape using a hot press at high temperature to obtain the negative electrode of the lithium battery; the negative electrode active material is at least one of graphite, lithium titanate, and silicon-carbon alloy; the conductive agent is at least one of acetylene black, conductive carbon black, and Super P; the mass ratio of the nano adhesive to the negative electrode active material is 1-3:17, and the mass ratio of the nano adhesive to the conductive agent is 1-2:1;

[0074] Step 10, stack the negative electrode sheet, separator, electrolyte drop, and positive electrode sheet from bottom to top, and use a hot press to form them into an integrated structure at high temperature. This method obtains nanoscale solid epoxy resin adhesive particles by using a double emulsion method and successful latent curing agent. The positive and negative electrode sheets are prepared by bonding the positive and negative electrode active materials to the current collector together with the conductive agent using the nano adhesive. High temperature treatment allows the solid spherical adhesive to self-adhere to form a film, thereby obtaining an epoxy resin-based lithium battery separator. The positive and negative electrode sheets and the battery separator are hot-pressed into an integrated lithium battery composite material in the order of lithium battery assembly.

[0075] Embodiment 1:

[0076] Step 1: 0.1 g of nano-Ag particles, 10 g of bisphenol A epoxy resin E44, 3.3 g of ethylene glycol diglycidyl ether, 2 g of maleic anhydride and 4 g of Span 80 were uniformly mixed and dispersed using a high-speed disperser at a speed of 2500 rpm to obtain a dispersion 1;

[0077] Step 2: Add 4 g of sodium chloride solution to the dispersion 1 at a constant speed, and stir at a high speed of 2500 rpm at 40°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0078] Step 3: at 40° C., 200 g of deionized water, 13.3 g of polyoxyethylene ether and 6.6 g of diethylenetriamine were uniformly mixed and dispersed using a high-speed disperser at 1000 rpm to obtain dispersion 2;

[0079] Step 4: Add 13.3 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1000 rpm to obtain a water-in-oil-in-water emulsion system;

[0080] Step 5. Heat the water-in-oil-in-water emulsion system to 60°C and continue stirring. The total heating and insulation reaction time is 25 minutes. A gradual gradient temperature increase is used to cure the epoxy spherical particles, rather than directly applying the optimal curing temperature of curing agent 2. This avoids the destruction of the water-in-oil-in-water emulsion by a sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution. In addition, gradual temperature increase curing is also beneficial to the control of the reaction rate, and it is easier to retain surface reactive groups;

[0081] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the residual emulsifier on the surface to obtain a nano conductive adhesive;

[0082] Step 7: Evenly mix 0.02g of nano-conductive adhesive, 0.34g of graphite, and 0.02g of acetylene black, grind them thoroughly, spread the mixed powder on aluminum foil, and press them at 160°C under 2MPa pressure for 3h using a hot press to obtain a dry-process lithium battery electrode. Hot pressing can not only make the thickness of the electrode sheet uniform, but also increase the compaction density of the negative electrode material. The appropriate compaction density can increase the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the lithium-ion battery.

[0083] Embodiment 2:

[0084] Step 1: 0.5 g of nano Au particles, 10 g of bisphenol A epoxy resin E51, 1.7 g of polyglycol diglycidyl ether, 3 g of 4,4'-diaminodiphenylmethane and 10 g of Span 60 were uniformly mixed and dispersed using a high-speed disperser at a speed of 3000 rpm to obtain a dispersion 1;

[0085] Step 2: drip 10g of sodium hydroxide solution into dispersion 1 at a constant speed, and stir at a high speed of 3000rpm at 60°C to obtain a water-in-oil emulsion. On the one hand, since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the aggregation of droplets. In addition, sodium hydroxide has a catalytic effect on the ring-opening reaction of epoxy resin epoxy groups, which can accelerate the formation of epoxy resin spherical particles.

[0086] Step 3: at 50° C., 200 g of deionized water, 10 g of OP-10 and 5 g of triethylenetetramine were uniformly mixed and dispersed using a high-speed disperser at 1500 rpm to obtain dispersion 2;

[0087] Step 4: add 10 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1500 rpm to obtain a water-in-oil-in-water emulsion system;

[0088] Step 5: heating the water-in-oil-in-water emulsion system to 80° C. and continuously stirring the system. The heating and heat preservation reaction time is 30 minutes in total, so as to control the epoxy resin balls to form nano-sized particles and retain more reactive groups.

[0089] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the residual emulsifier on the surface to obtain a nano conductive adhesive;

[0090] Step 7: Evenly mix 0.06g of nano-conductive adhesive, 0.34g of lithium titanate, and 0.03g of conductive carbon black, grind them thoroughly, spread the mixed powder on aluminum foil, and use a hot press to press at 80°C and 2MPa for 2h, and then continue pressing at 160°C and 2MPa for 2 hours to obtain a dry-process lithium battery electrode. Hot pressing can not only make the thickness of the electrode sheet uniform, but also increase the compaction density of the negative electrode material. The appropriate compaction density can increase the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the lithium-ion battery.

[0091] Embodiment 3:

[0092] Step 1: 0.08 g of graphene, 0.08 g of carbon fiber, 10 g of epoxy resin 711#, 1.25 g of butyl glycidyl ether, 1.25 g of polyglycol diglycidyl ether, 2.5 g of m-phenylenediamine and 6 g of Span 40 were uniformly mixed and dispersed using a high-speed disperser at a speed of 2700 rpm to obtain a dispersion 1;

[0093] Step 2: Add 4 g NH3·H2O-NH4Cl buffer and 4 g potassium chloride solution to dispersion 1 at a constant rate, and stir at 2700 rpm at 50°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0094] Step 3: at 45° C., 200 g of deionized water, 6 g of polyvinyl alcohol, 6 g of OP-10, 3 g of triethylenetetramine and 3 g of tetraethylenepentamine were uniformly mixed and dispersed using a high-speed disperser at 1300 rpm to obtain dispersion 2;

[0095] Step 4: Add 12 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1300 rpm to obtain a water-in-oil-in-water emulsion system;

[0096] Step 5: heating the water-in-oil-in-water emulsion system to 70° C. and continuously stirring the system. The heating and heat preservation reaction time is 27 minutes in total, so as to control the epoxy resin balls to form nano-sized particles and retain more reactive groups.

[0097] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the residual emulsifier on the surface to obtain a nano conductive adhesive;

[0098] Step 7: Evenly mix 0.04g of nano-conductive adhesive, 0.34g of silicon-carbon alloy, and 0.026g of Super P, grind them thoroughly, spread the mixed powder on aluminum foil, and use a hot press to press at 80°C and 2MPa for 2h, and then continue pressing at 150°C and 2MPa for 2 hours to obtain a dry-process lithium battery electrode. Hot pressing can not only make the thickness of the electrode sheet uniform, but also increase the compaction density of the negative electrode material. The appropriate compaction density can increase the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the lithium-ion battery.

[0099] Figure 1 The dry method is used to prepare lithium battery electrodes. As shown in the figure, the lithium battery electrodes in the present invention are evenly distributed on the aluminum foil and are firmly bonded.

[0100] Figure 2 This is the cyclic voltammetry curve of the dry-type lithium battery electrode. As shown in the figure, the battery cycle is relatively stable after three cycles of activation.

[0101] Embodiment 4:

[0102] Step 1: 10 g of bisphenol A epoxy resin E44, 3.3 g of ethylene glycol diglycidyl ether, 2 g of maleic anhydride and 4 g of Span 80 were uniformly mixed and dispersed using a high-speed disperser at a speed of 2500 rpm to obtain a dispersion 1;

[0103] Step 2: Add 4 g of sodium chloride solution to the dispersion 1 at a constant speed, and stir at a high speed of 2500 rpm at 40°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0104] Step 3: at 40° C., 200 g of deionized water, 13.3 g of polyoxyethylene ether and 6.6 g of diethylenetriamine were uniformly mixed and dispersed using a high-speed disperser at 1000 rpm to obtain dispersion 2;

[0105] Step 4: Add 13.3 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1000 rpm to obtain a water-in-oil-in-water emulsion system;

[0106] Step 5. Heat the water-in-oil-in-water emulsion system to 60°C and continue stirring. The total heating and insulation reaction time is 25 minutes. A gradual gradient temperature increase is used to cure the epoxy spherical particles, rather than directly applying the optimal curing temperature of curing agent 2. This avoids the destruction of the water-in-oil-in-water emulsion by a sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution. In addition, gradual temperature increase curing is also beneficial to the control of the reaction rate, and it is easier to retain surface reactive groups;

[0107] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0108] Step 7: Grind 0.02g of solid nano adhesive, then use a coating knife to control the film thickness to 0.05mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3 In a stainless steel mold, after being treated at 160°C for 3 hours at 1 MPa using a hot press, the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0109] Embodiment 5:

[0110] Step 1: 10 g of bisphenol A epoxy resin E51, 1.7 g of polyglycol diglycidyl ether, 3 g of 4,4'-diaminodiphenylmethane and 10 g of Span 60 were uniformly mixed and dispersed at a speed of 3000 rpm using a high-speed disperser to obtain a dispersion 1;

[0111] Step 2: drip 10g of sodium hydroxide solution into dispersion 1 at a constant speed, and stir at a high speed of 3000rpm at 60°C to obtain a water-in-oil emulsion. On the one hand, since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the aggregation of droplets. In addition, sodium hydroxide has a catalytic effect on the ring-opening reaction of epoxy resin epoxy groups, which can accelerate the formation of epoxy resin spherical particles.

[0112] Step 3: at 50° C., 200 g of deionized water, 10 g of OP-10 and 5 g of triethylenetetramine were uniformly mixed and dispersed using a high-speed disperser at 1500 rpm to obtain dispersion 2;

[0113] Step 4: add 10 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1500 rpm to obtain a water-in-oil-in-water emulsion system;

[0114] Step 5: heating the water-in-oil-in-water emulsion system to 80° C. and continuously stirring the system. The heating and heat preservation reaction time is 30 minutes in total, so as to control the epoxy resin balls to form nano-sized particles and retain more reactive groups.

[0115] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0116] Step 7: Grind 0.05g of solid nano adhesive, then use a coating knife to control the film thickness to 0.1mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3 In a stainless steel mold, after high-temperature treatment at 80°C for 2 hours and 160°C for 2 hours at 2MPa using a hot press, the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0117] Embodiment 6:

[0118] Step 1: 10 g of epoxy resin 711#, 1.25 g of butyl glycidyl ether, 1.25 g of polyglycol diglycidyl ether, 2.5 g of m-phenylenediamine and 6 g of Span 40 were uniformly mixed and dispersed at a speed of 2700 rpm using a high-speed disperser to obtain a dispersion 1;

[0119] Step 2: Add 4 g NH3·H2O-NH4Cl buffer and 4 g potassium chloride solution to dispersion 1 at a constant rate, and stir at 2700 rpm at 50°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0120] Step 3: at 45° C., 200 g of deionized water, 6 g of polyvinyl alcohol, 6 g of OP-10, 3 g of triethylenetetramine and 3 g of tetraethylenepentamine were uniformly mixed and dispersed using a high-speed disperser at 1300 rpm to obtain dispersion 2;

[0121] Step 4: Add 12 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1300 rpm to obtain a water-in-oil-in-water emulsion system;

[0122] Step 5. Heat the water-in-oil-in-water emulsion system to 70°C and continue stirring. The total heating and insulation reaction time is 27 minutes. A gradual gradient temperature increase is used to cure the epoxy spherical particles, rather than directly applying the optimal curing temperature of curing agent 2. This avoids the destruction of the water-in-oil-in-water emulsion by a sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution. In addition, gradual temperature increase curing is also beneficial to the control of the reaction rate, and it is easier to retain surface reactive groups;

[0123] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0124] Step 7: Grind 0.03g of solid nano adhesive, then use a coating knife to control the film thickness to 0.07mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3 In a stainless steel mold, after high-temperature treatment at 80°C for 2 hours and 150°C for 2 hours at 1.5 MPa using a hot press, the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0125] Figure 3 The SEM image of the nano adhesive is shown in FIG. 1 . As shown in the figure, the particle size of the solid nano adhesive in the present invention is about 50 nm at the minimum, and it presents a regular spherical shape.

[0126] Figure 4 The lithium battery separator obtained by self-adhesion of solid nano adhesive. As shown in the figure, the solid adhesive can successfully self-adhere to form a film with uniform thickness under high temperature and hot pressure.

[0127] Figure 5 This is a SEM image of a lithium battery separator obtained by self-adhesion of a solid nano-adhesive. As shown in the figure, the lithium battery separator has a high porosity, which is beneficial to the ion exchange in the operation of the lithium battery.

[0128] Embodiment 7:

[0129] Step 1: 10 g of bisphenol A epoxy resin E44, 3.3 g of ethylene glycol diglycidyl ether, 2 g of maleic anhydride and 4 g of Span 80 were uniformly mixed and dispersed using a high-speed disperser at a speed of 2500 rpm to obtain a dispersion 1;

[0130] Step 2: Add 4 g of sodium chloride solution to the dispersion 1 at a constant speed, and stir at a high speed of 2500 rpm at 40°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0131] Step 3: at 40° C., 200 g of deionized water, 13.3 g of polyoxyethylene ether and 6.6 g of diethylenetriamine were uniformly mixed and dispersed using a high-speed disperser at 1000 rpm to obtain dispersion 2;

[0132] Step 4: Add 13.3 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1000 rpm to obtain a water-in-oil-in-water emulsion system;

[0133] Step 5. Heat the water-in-oil-in-water emulsion system to 60°C and continue stirring. The total heating and insulation reaction time is 25 minutes. A gradual gradient temperature increase is used to cure the epoxy spherical particles, rather than directly applying the optimal curing temperature of curing agent 2. This avoids the destruction of the water-in-oil-in-water emulsion by a sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution. In addition, gradual temperature increase curing is also beneficial to the control of the reaction rate, and it is easier to retain surface reactive groups;

[0134] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0135] Step 7: Evenly mix 0.02g of nano adhesive, 0.34g of lithium manganate, and 0.02g of acetylene black and grind them thoroughly, spread the mixed powder on aluminum foil, and press it at 160°C under 2MPa pressure for 1.5h (half of the time for maleic anhydride to completely cure, to maintain a certain reaction activity for the final battery assembly) using a hot press to obtain a lithium battery positive electrode prepared by a dry method. Hot pressing can not only make the thickness of the electrode sheet uniform, but also increase the compaction density of the negative electrode material. The appropriate compaction density can increase the discharge capacity of the battery, reduce the internal resistance, reduce the polarization loss, extend the cycle life of the battery, and improve the utilization rate of the lithium-ion battery.

[0136] Step 8. Evenly mix 0.02g of nano-adhesive, 0.34g of graphite and 0.02g of acetylene black and grind them thoroughly. Spread the mixed powder onto copper foil and press it at 160°C under a pressure of 2MPa for 1.5 hours (half of the time required for complete curing of maleic anhydride to maintain a certain reaction activity for the final battery assembly) using a hot press to obtain a lithium battery negative electrode prepared by a dry method.

[0137] Step 9: Grind 0.02g of solid nano adhesive, then use a coating knife to control the film thickness to 0.05mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3In a stainless steel mold, after being treated at 160°C at 1MPa for 1.5 hours using a hot press (half the time it takes for maleic anhydride to fully cure, to maintain a certain reactivity for the final battery assembly), the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0138] Step 10: stack the negative electrode sheet, separator, electrolyte solution and positive electrode sheet from bottom to top in this order, and use a hot press to heat-press them into an integrated unit after high-temperature treatment at 160°C for 1.5 hours at 2MPa.

[0139] Embodiment 8:

[0140] Step 1: 10 g of bisphenol A epoxy resin E51, 1.7 g of polyglycol diglycidyl ether, 3 g of 4,4'-diaminodiphenylmethane and 10 g of Span 60 were uniformly mixed and dispersed at a speed of 3000 rpm using a high-speed disperser to obtain a dispersion 1;

[0141] Step 2: drip 10g of sodium hydroxide solution into dispersion 1 at a constant speed, and stir at a high speed of 3000rpm at 60°C to obtain a water-in-oil emulsion. On the one hand, since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the aggregation of droplets. In addition, sodium hydroxide has a catalytic effect on the ring-opening reaction of epoxy resin epoxy groups, which can accelerate the formation of epoxy resin spherical particles.

[0142] Step 3: at 50° C., 200 g of deionized water, 10 g of OP-10 and 5 g of triethylenetetramine were uniformly mixed and dispersed using a high-speed disperser at 1500 rpm to obtain dispersion 2;

[0143] Step 4: add 10 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1500 rpm to obtain a water-in-oil-in-water emulsion system;

[0144] Step 5: heating the water-in-oil-in-water emulsion system to 80° C. and continuously stirring the system. The heating and heat preservation reaction time is 30 minutes in total, so as to control the epoxy resin balls to form nano-sized particles and retain more reactive groups.

[0145] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0146] Step 7: Evenly mix 0.06g of nano-adhesive, 0.34g of lithium cobalt oxide, and 0.03g of conductive carbon black and grind them thoroughly. Spread the mixed powder onto aluminum foil and press at 80°C and 2MPa for 2 hours to obtain a lithium battery positive electrode prepared by a dry method.

[0147] Step 8: Evenly mix 0.06g of nano-adhesive, 0.34g of lithium titanate, and 0.03g of conductive carbon black and grind them thoroughly. Spread the mixed powder onto copper foil and press at 80°C and 2MPa for 2 hours to obtain a lithium battery negative electrode prepared by a dry method.

[0148] Step 9: Grind 0.05g of solid nano adhesive, then use a coating knife to control the film thickness to 0.1mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3 In a stainless steel mold, after being treated at 80°C for 2 hours at 2MPa using a hot press, the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0149] Step 10: From bottom to top, stack the negative electrode sheet, separator, electrolyte solution, and positive electrode sheet in this order, and use a hot press to heat-press them at 160°C for 2 hours at 2MPa. (The complete curing process of 4,4'-diaminodiphenylmethane is 80°C for 2 hours plus 160°C for 2 hours. The temperature during the preparation of the positive and negative electrode sheets and separator is only 80°C to maintain a certain degree of reaction activity for the final battery assembly.)

[0150] Embodiment 9:

[0151] Step 1: 10 g of epoxy resin 711#, 1.25 g of butyl glycidyl ether, 1.25 g of polyglycol diglycidyl ether, 2.5 g of m-phenylenediamine and 6 g of Span 40 were uniformly mixed and dispersed at a speed of 2700 rpm using a high-speed disperser to obtain a dispersion 1;

[0152] Step 2: Add 4 g NH3·H2O-NH4Cl buffer and 4 g potassium chloride solution to dispersion 1 at a constant rate, and stir at 2700 rpm at 50°C to obtain a water-in-oil emulsion. Since the electrolyte solution is the internal water phase of the emulsion, it will increase the osmotic pressure inside the emulsion and avoid the coalescence of droplets;

[0153] Step 3: at 45° C., 200 g of deionized water, 6 g of polyvinyl alcohol, 6 g of OP-10, 3 g of triethylenetetramine and 3 g of tetraethylenepentamine were uniformly mixed and dispersed using a high-speed disperser at 1300 rpm to obtain dispersion 2;

[0154] Step 4: Add 12 g of the water-in-oil emulsion to the dispersion 2, and emulsify at a high speed of 1300 rpm to obtain a water-in-oil-in-water emulsion system;

[0155] Step 5. Heat the water-in-oil-in-water emulsion system to 70°C and continue stirring. The total heating and insulation reaction time is 27 minutes. A gradual gradient temperature increase is used to cure the epoxy spherical particles, rather than directly applying the optimal curing temperature of curing agent 2. This avoids the destruction of the water-in-oil-in-water emulsion by a sudden temperature rise. The emulsification effect of the emulsifier is generally sensitive to temperature changes. When the temperature exceeds the critical point, the emulsification effect is destroyed, and the emulsion droplets break or aggregate, resulting in a large final particle size and uneven distribution. In addition, gradual temperature increase curing is also beneficial to the control of the reaction rate, and it is easier to retain surface reactive groups;

[0156] Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to remove the emulsifier remaining on the surface to obtain a solid nano adhesive;

[0157] Step 7: Evenly mix 0.04g of nano-adhesive, 0.34g of nickel-cobalt-manganese ternary material, and 0.026g of Super P and grind them thoroughly. Spread the mixed powder on aluminum foil and press at 80°C and 2MPa for 2 hours to obtain a lithium battery positive electrode prepared by a dry method.

[0158] Step 8: Evenly mix 0.04 g of nano-adhesive, 0.34 g of silicon-carbon alloy, and 0.026 g of Super P, grind them thoroughly, spread the mixed powder on copper foil, and press at 80° C. and 2 MPa for 2 hours to obtain a lithium battery negative electrode prepared by a dry method.

[0159] Step 9: Grind 0.03g of solid nano adhesive, then use a coating knife to control the film thickness to 0.07mm, and evenly spread the adhesive on the groove size of 40*40*10mm. 3 In a stainless steel mold, after being treated at 80°C for 2 hours at 1.5 MPa using a hot press, the epoxy resin solid adhesive can self-bond to obtain a lithium battery separator.

[0160] Step 10: From bottom to top, stack the negative electrode sheet, separator, electrolyte solution, and positive electrode sheet in this order, and use a hot press to heat-press them at 150°C for 2 hours at 2MPa to form an integrated structure. (The complete curing process of m-phenylenediamine is 80°C for 2 hours plus 150°C for 2 hours. The temperature during the preparation of the positive and negative electrode sheets and separator is only 80°C to maintain a certain reaction activity for the final battery assembly). Figure 6 Schematic diagram of the battery-structure integrated composite material structure.

Claims

1. A method for preparing a lithium battery-structure integrated composite material, characterized in that: The method steps are: Step 1, uniformly mixing and dispersing the epoxy resin, the diluent, the curing agent 1 and the lipophilic emulsifier to obtain a dispersion 1; Step 2: dripping the electrolyte solution into the dispersion 1 at a constant speed, stirring at a constant temperature and high speed to obtain a water-in-oil emulsion; Step 3: at a constant temperature, uniformly mix and disperse deionized water, a hydrophilic emulsifier and a curing agent 2 to obtain a dispersion 2; Step 4: adding the water-in-oil emulsion to the dispersion 2, and continuously stirring and emulsifying at a high speed to obtain a water-in-oil-in-water emulsion system; Step 5: heating the water-in-oil-in-water emulsion system, stirring continuously, and solidifying; Step 6: centrifuging, washing and drying the solidified water-in-oil-in-water emulsion system to obtain a solid nano-adhesive; Step 7: Grind the solid nano adhesive, then evenly spread it in a stainless steel groove mold, and use a hot press to perform high-temperature treatment under a certain pressure to obtain a lithium battery separator; Step 8: uniformly mix and fully grind the solid nano adhesive, the positive electrode active material, and the conductive agent, spread the mixed powder on the aluminum foil, and press the mixture into a shape using a hot press at high temperature to obtain a positive electrode of a lithium battery; the mass ratio of the solid nano adhesive to the positive electrode active material is 1-3:17, and the mass ratio of the solid nano adhesive to the conductive agent is 1-2:1; Step nine: uniformly mix and fully grind the solid nano adhesive, the negative electrode active material, and the conductive agent, spread the mixed powder on the copper foil, and press the mixture into a shape using a hot press at high temperature to obtain the negative electrode of the lithium battery; the mass ratio of the solid nano adhesive to the negative electrode active material is 1-3:17, and the mass ratio of the solid nano adhesive to the conductive agent is 1-2:1; Step 10: stack the negative electrode sheet of the lithium battery, the lithium battery separator, the electrolyte solution, and the positive electrode sheet of the lithium battery from bottom to top, and use a hot press to perform integrated hot pressing at high temperature.

2. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step one, the epoxy resin is at least one of bisphenol A epoxy resin, glycidyl ester epoxy resin and alicyclic epoxy resin; the diluent is at least one of ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether and butyl glycidyl ether; the curing agent 1 is one or a mixture of maleic anhydride, phthalic anhydride, m-phenylenediamine, 3,3'-diethyl-4,4'-diaminodiphenylmethane and 4,4'-diaminodiphenylmethane; the lipophilic emulsifier is at least one of Span 20, Span 40, Span 60 and Span 80.

3. The method for preparing a lithium battery-structure integrated composite material according to claim 2, characterized in that: In step 1, the bisphenol A type epoxy resin is at least one of E55, E51 and E44; the glycidyl ester epoxy resin is at least one of 711#, TDE-85# and 731#; the alicyclic epoxy resin is at least one of W-95#, 6221# and 6206#.

4. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step 1, the mass ratio of the epoxy resin to the diluent is 3-6:1; the mass ratio of the epoxy resin to the curing agent 1 is 10:2-3; the mass ratio of the epoxy resin to the lipophilic emulsifier is 5:2-5.

5. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step 2, the mass ratio of the epoxy resin to the electrolyte solution is 5:2-5.

6. A method for preparing a lithium battery-structure integrated composite material according to claim 1 or 5, characterized in that: In step 2, the electrolyte solution is at least one of a 0.1 mol / L sodium chloride solution, a 0.1 mol / L potassium chloride solution, a pH=10 NH3·H2O-NH4Cl buffer solution and a 0.1 mol / L sodium hydroxide solution.

7. A method for preparing a lithium battery-structure integrated composite material according to claim 1 or 5, characterized in that: In step 2, the constant reaction temperature is 40-60°C, the time is 10-15min, and the stirring speed is 2500-3000rpm; in step 3, the initial temperature is 40-50°C; in step 5, the temperature is raised to 60-80°C, and the heating process and insulation reaction are 25-30 minutes in total; the stirring speed is 1000-1500rpm; in step 7, the amount of solid nano adhesive is 0.02-0.05g; the high temperature is the curing temperature of curing agent 1; the size of the stainless steel mold groove is 40*40*10mm 3 ; When evenly coating the nano adhesive, use a coating knife to initially control its thickness to 0.05-0.1mm; the hot press pressure is 1-2MPa.

8. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step three, the hydrophilic emulsifier is one of a nonionic emulsifier and an anionic emulsifier or a mixture thereof; the nonionic emulsifier is at least one of polyoxyethylene ether, OP-10 and polyvinyl alcohol; the anionic emulsifier is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and phosphate; the curing agent 2 is one of ethylenediamine, diethylenetriamine, triethylenetetramine and tetraethylenepentamine or a mixture thereof.

9. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step three, the mass ratio of the deionized water to the hydrophilic emulsifier is 15-20:1; the mass ratio of the nonionic emulsifier to the anionic emulsifier is 20:0-3; and the mass ratio of the deionized water to the curing agent 2 is 30-40:

1.

10. The method for preparing a lithium battery-structure integrated composite material according to claim 1, characterized in that: In step 4, the mass ratio of deionized water to water-in-oil emulsion is 15-20:1.

Citation Information

Patent Citations

  • Cylindrical high-capacity low-temperature lithium ion battery

    CN109509881A

  • Integrated flexible lithium-ion battery and preparation method thereof

    CN110808406A

  • PMMA (polymethyl methacrylate) cross-linked spherical micro-powder coating diaphragm, preparation method thereof and application of diaphragm in lithium ion battery

    CN112038549A

  • Nonaqueous electrolyte power storage device, and method for manufacturing the same

    JP2013020957A

  • Ceramic Nanowire Battery Separators

    US20210344080A1

Cited By

  • Preparation method of lithium battery diaphragm

    CN119864595A

  • A method for preparing a lithium battery separator

    CN119864595B